Genome-wide analysis of terpene synthase gene family to explore candidate genes related to disease resistance in Prunus persica - Li, Xiongwei; Hu, Yang; Su, Mingshen; Zhang, Minghao; Du, Jihong; Zhou, Huijuan; Zhang, Xianan; Ye, Zhengwen (Frontiers in Plant Science, 2022)
In plants, a family of terpene synthases (TPSs) is responsible for the biosynthesis of terpenes and contributes to species-specific diversity of volatile organic compounds, which play essential roles in fitness of plants. However, little is known about the TPS gene family in peach and/or nectarine (Prunus persica L.). In this study, we identified 40 PpTPS genes in peach genome v2.0. Although these PpTPSs could be clustered into five classes, they distribute in several gene clusters of three chromosomes, share conserved exon-intron organizations, and code similar protein motifs. Thirty-five PpTPSs, especially PpTPS2, PpTPS23, PpTPS17, PpTPS18, and PpTPS19, altered their transcript levels after inoculation with Botryosphaeria dothidea, a cause of peach gummosis, compared to the mock treatments, which might further affect the contents of 133 terpenoids at 48 hours and/or 84 hours post inoculations in the current-year shoots of ‘Huyou018’, a highly susceptible nectarine cultivar. Moreover, about fifteen PpTPSs, such as PpTPS1, PpTPS2, PpTPS3, and PpTPS5, showed distinct expression patterns during fruit development and ripening in two peach cultivars, yellow-fleshed ‘Jinchun’ and white-fleshed ‘Hikawa Hakuho’. Among them, the transcription level of chloroplast-localized PpTPS3 was obviously related to the content of linalool in fruit pulps. In addition, elevated concentrations (0.1 g/L to 1.0 g/L) of linalool showed antifungal activities in PDA medium. These results improve our understanding of peach PpTPS genes and their potential roles in defense responses against pathogens.